2018
DOI: 10.3233/jad-180164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Meditation and Music-Listening on Blood Biomarkers of Cellular Aging and Alzheimer’s Disease in Adults with Subjective Cognitive Decline: An Exploratory Randomized Clinical Trial

Abstract: Background: Telomere length (TL), telomerase activity (TA), and plasma amyloid-β(Aβ) levels have emerged as possible predictors of cognitive decline and dementia. Objective: To assess the: 1) effects of two 12-week relaxation programs on TL, TA, and Aβ levels in adults with subjective cognitive decline; and 2) relationship of biomarker changes to those in cognitive function, psychosocial status, and quality of life (QOL). Methods: Participants were randomized to a 12-week Kirtan Kriya meditation (KK) or mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(104 citation statements)
references
References 150 publications
2
90
3
2
Order By: Relevance
“…Several recent reviews of meditation interventions (of either Kirtan Kriya Meditation or mindfulness-based programs) [64] and yoga interventions [65] report on 11 additional studies [66][67][68][69][70][71][72][73][74][75][76][77][78] that have demonstrated benefits in adults with subjective cognitive decline, MCI, and AD. Since these reviews, an additional study of tai chi in older adults at risk for cognitive decline has been published, [79] along with mindfulness studies in adults with subjective cognitive decline, [80,81] MCI, [82] and dementia. [83,84] The study designs and outcomes from these studies are very heterogeneous, and most studies were small and considered pilot/feasibility (except for two studies with sample sizes over 110 [70,79]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent reviews of meditation interventions (of either Kirtan Kriya Meditation or mindfulness-based programs) [64] and yoga interventions [65] report on 11 additional studies [66][67][68][69][70][71][72][73][74][75][76][77][78] that have demonstrated benefits in adults with subjective cognitive decline, MCI, and AD. Since these reviews, an additional study of tai chi in older adults at risk for cognitive decline has been published, [79] along with mindfulness studies in adults with subjective cognitive decline, [80,81] MCI, [82] and dementia. [83,84] The study designs and outcomes from these studies are very heterogeneous, and most studies were small and considered pilot/feasibility (except for two studies with sample sizes over 110 [70,79]).…”
Section: Discussionmentioning
confidence: 99%
“…Shorter meditation interventions (such as with Kirtan Kriya) have shown positive outcomes in quality of life and cognition in adults with subjective cognitive decline. [80,81] Future studies could compare such shorter meditation interventions (such as with Kirtan Kriya meditation) to MBSR in adults with MCI to assess if shorter programs may provide the same benefits seen in this study. Given such limitations, many are looking for more time-efficient ways to learn mindfulness and ways to increase access.…”
Section: Limitations and Future Directionsmentioning
confidence: 91%
“…Several interventions have been previously studied for preventing cognitive and physical decline and maintaining physical performance, mobility and independence in the elderly such as a healthy lifestyle [7,8], meditation [9][10][11], cognitive training [12], pharmaceuticals [13], plant extracts [14][15][16][17] and nutraceuticals [14,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, differences between normal aging and MCI appear to be driven in large measure by amyloid-β burden [ 77 ]. Of note is that KK may decrease brain amyloid-β burden as evidenced by increased plasma amyloid-β [ 61 ].…”
Section: Kirtan Kriya: the Bridge Between Stress And Spiritual Fitnessmentioning
confidence: 99%